Generalized Disappointment Aversion, Rare Disasters, and the Term Structure of Real Interest Rates - Wang, Shanshan (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2025)
This study models a representative agent with generalized disappointment aversion preferences in an endowment economy. This model addresses the average upward slope in U.S. real bond yields, equity premium puzzle, and equity volatility puzzle. We integrate a two-state Markov switching process for economic cycles coupled with an independent rare disaster risk. During economic expansions, disaster risk increases the probability of disappointment, thereby reinforcing precautionary saving and reducing the risk-free rate. During recessions, diminished concern about disappointment encourages borrowing and increases the risk-free rate. This pattern engenders countercyclical fluctuations in risk-free rates and accounts for the upward-sloping average yield curve.